Influence of Entrepreneurial Management on the Growth of Small and Medium Tour Firms in Kenya - Kinyua, Jesse M.; Kimani, Anthony (My University, 2015)
This study focused on proprietors and business development managers of the 367 tour companies in Kenya members of Kenya Association of Tour Operators (KATO). The sample size was 256 proprietors and business development managers who were selected randomly from the population. To collect primary data a semi-structured questionnaire with both close-ended and open-ended questions was used. A pre-test was conducted to increase the reliability and validity of the data collection tool. The data collected was then analyzed using descriptive statistics. The researcher further employed a multivariate regression model to study the relationship between entrepreneurial management and growth of small and medium tour companies in Kenya. The study established that entrepreneurial management influences growth of business in the tour companies to a great extent. The study has also illustrated that resource gap identification, opportunity commitment, and social capital development and growth orientation influences growth of business of the small and medium tour companies in Kenya to a great extent. The study recommends that firms should in place mechanism to seek to establish slack in performance as a result of resources inadequacies, seizes any promising business opportunity, develop social capital to ensure business growth and continuity, and effect changes in the management systems employed in search of growth.